1994
DOI: 10.1111/j.1365-2249.1994.tb06031.x
|View full text |Cite
|
Sign up to set email alerts
|

Avidity of Aspergillus umbrosus IgG antibodies in farmer's lung disease

Abstract: SUMMARYFarmer's lung disease (FL)-the commonest form of allergic alveolitis caused by repeated inhalation of mouldy hay. is associated with exposure lo the fungus Aspergithis umbrosus among Einnish farmers. The antigen-binding avidity of A. j/mA/asM.s-specific IgG antibodies was measured in 12 EL patients in acute phases of initial and recurrent attacks and during 1 year foliow up as well as in 12 healthy farmers and five healthy urban controls. The farmers* groups were further divided into two subgroups: subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Hypersensitivity pneumonitis (allergic alveolitis) results from inhalation of large numbers of spores, and causes flu-like symptoms, coughing and chest tightness 4-6 hours after exposure. These include malt worker's lung (A. clavatus and A. fumigatus), air-conditioning disease (A. fumigatus) (Stevens, 1987), and farmer's lung (A. umbosus and others, Kaukonen et al, 1994).…”
Section: Allergiesmentioning
confidence: 99%
“…Hypersensitivity pneumonitis (allergic alveolitis) results from inhalation of large numbers of spores, and causes flu-like symptoms, coughing and chest tightness 4-6 hours after exposure. These include malt worker's lung (A. clavatus and A. fumigatus), air-conditioning disease (A. fumigatus) (Stevens, 1987), and farmer's lung (A. umbosus and others, Kaukonen et al, 1994).…”
Section: Allergiesmentioning
confidence: 99%
“…However, this finding was not further evaluated to define a threshold by ROC curve analysis for the serodiagnosis of FLD, as described in our study. Kaukonen et al (1993) carried out Western blotting with antigenic proteins from Aspergillus umbrosus. Similar to the findings of Aznar et al (1988), they reported that signals observed with FLD sera were of a higher intensity than signals detected with HEC sera.…”
Section: Band Intensitymentioning
confidence: 99%
“…Conditions such as chronic hypersensitive pneumonitis or pulmonary mycotoxicosis (farmer's lung) are often related to occupation (Kaukonen et al, 1994(Kaukonen et al, , 1996Hjort et al, 20 1986). Allergy or hypersensitivity can be described as an immune response against a foreign antigen that is exaggerated beyond the norm.…”
Section: Health Effects Related To Indoor Fungimentioning
confidence: 99%
“…Eurotium amstelodami is believed to cause farmer's lung -a common form of hypersensitive pneumonia (Kaukonen et al, 1994;Hjort et al, 1986) and may evolve into end-stage lung disease (Lacasse, 2003). It can result from repeated exposures to high concentrations or prolonged exposures to low concentration of inhaled allergens from mold-covered straw and hay to which the patient has previously been sensitized (Fenoglio, 2007;Radon, 2002;Roussel et al, 2010).…”
Section: Health Issues Related To Eurotium Speciesmentioning
confidence: 99%